The Notion of ‘Effortlessness’ in the Dzogchen Commentaries by Nubchen Sangye Yeshe - Esler, Dylan (Entangled Religions, 2023)
The present contribution will seek to explore the notion of effortlessness in the Dzogchen commentaries by Nubchen Sangye Yeshe (ca. 844-mid-tenth century), examining its role as a key theme in the self-understanding of the emergent Dzogchen tradition’s approach to contemplative practice. We will also touch upon the (apparent?) paradox consisting of learning the meditative skill of uncontrived effortlessness, where the process of meditative training and the content or ideal of this training are supposed to coalesce.